Study Perilaku Risiko, Literasi Keuangan Dan Perilaku Keuangan Terhadap Keputusan Investasi - Virgirio Jeremmy Ramadani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The purpose of this study was to determine the effect of financial literacy and perceived risk on investment decisions through financial behavior as intervening variables in stock investors in Solo Raya. The method used in the sampling was purposive sampling technique with 400 respondents. Data collection was carried out by distributing questionnaires via the Google form. The analysis technique used is PLS (Partial Least Square) analysis through the Smart PLS 4 program. The results show (1) Perceived risk has a significant positive effect on financial behavior (2) Perceived risk has a significant positive effect on investment decisions, (3) Financial literacy has a positive effect significant effect on financial behavior. (4) Financial literacy has a significant positive effect on investment decisions, (5) Financial behavior has a significant positive effect on investment decisions, (6) Perceived risk has a significant positive effect on investment decisions through financial behavior, (7) Financial literacy has a significant effect significant positive effect on investment decisions through financial behavior, financial behavior.